EMPLOYEE ENGAGEMENT MEDIATION MODEL: AN ANALYSIS OF THE INFLUENCE OF WORK CULTURE AND LEADERSHIP ON THE PERFORMANCE OF ASN IN SITUBONDO REGENCY GOVERNMENT - Rohmatul Maula; Nursaid Nursaid; Toni Herlambang (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the role of employee engagement as a mediating variable in the influence of work culture and leadership on the performance of the State Civil Apparatus (ASN) within the Situbondo Regency Government, considering that there are still problems with ASN performance that are not optimal. This study uses a quantitative descriptive approach with a population of 6,904 employees, and a research sample of 100 respondents was determined using the Slovin formula with purposive sampling techniques. Data was collected through questionnaires, interviews, observations, and literature studies, then analyzed using Structural Equation Modeling (SEM) with the WarpPLS 8.0 application. The results of the study show that work culture has a significant effect on employee engagement and employee performance, while leadership does not have a significant effect on employee engagement but has a significant effect directly on employee performance. Employee engagement has been proven to have a significant effect on employee performance and is able to mediate the influence of work culture on ASN performance significantly. In contrast, employee engagement is not able to mediate the influence of leadership on employee performance. These findings indicate that a positive work culture is a key factor in building employee attachment which further has an impact on improving ASN performance. This research provides practical implications for the Situbondo Regency Government to prioritize strengthening work culture and increasing employee engagement as the main strategy in improving the performance of ASN in a sustainable manner